2019
DOI: 10.1016/j.wjorl.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CT and MRI in assessment of mandibular involvement in oral cavity cancer

Abstract: Objective Oral cavity squamous cell carcinoma (SCC) may present with early invasion of mandibular bone. Preoperative planning of surgery is essential considering patient's postoperative quality of life. Our purpose was to evaluate the efficacy of computer tomography scan (CT) and magnetic resonance imaging (MRI) in detecting mandibular bone involvement in oral SCC. Methods A retrospective study was conducted on 98 patients with SCC of floor of mouth, lower alveolus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…MRI, capable of detecting alterations in the mandible’s bone marrow signal, stands out as one of the most effective morphological imaging tools for identifying bone invasion in OSCC. Its high sensitivity and negative predictive value have been well-documented [5,22]. MRI images with positive findings for bone invasion can be instrumental in ruling out bone marrow invasion when CT scans are negative [23].…”
Section: Discussionmentioning
confidence: 99%
“…MRI, capable of detecting alterations in the mandible’s bone marrow signal, stands out as one of the most effective morphological imaging tools for identifying bone invasion in OSCC. Its high sensitivity and negative predictive value have been well-documented [5,22]. MRI images with positive findings for bone invasion can be instrumental in ruling out bone marrow invasion when CT scans are negative [23].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative imaging is important. There are some instrumental exams that should be practiced to understand the size and the stage of the pathology and to define the surgical and/or the medical therapy (Nae et al , 2019). Sometimes of these exams may require long times to be practiced because long waiting lists in the hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…For detecting mandibular invasion, Vidiri et al reported 94% sensitivity and 60% specificity [114]. A subsequent study by Nae et al demonstrated that combining MRI with CT improved diagnostic efficacy (100% sensitivity and 72% specificity) [115]. However, false negatives were high and attributed to minor cortical inflammatory changes unrelated to the tumor and improper sampling of cortical bone.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%